2017
DOI: 10.1590/1678-98652017000500007
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast and associated factors among Brazilian adolescents

Abstract: A B S T R A C T ObjectiveTo analyze the prevalence and factors associated with breakfast skipping among adolescents. MethodsCross-sectional study, with adolescents aged 10-17 years, evaluated between 2009 and 2011, belonging to a cohort study in the Central-West region of Brazil. Breakfast skipping was considered as not having breakfast every day. Demographic, socioeconomic, and lifestyle factors were evaluated through a questionnaire. Anthropometric assessment included measurement of weight and height, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
(63 reference statements)
3
15
3
Order By: Relevance
“…Furthermore, the present study revealed that girls skipped breakfast more than boys, which is congruent with the available evidence (Fiuza et al, ; Moreno‐Maldonado et al, ; Smith et al, ). Indeed, in our study, gender was among the significant predictors.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, the present study revealed that girls skipped breakfast more than boys, which is congruent with the available evidence (Fiuza et al, ; Moreno‐Maldonado et al, ; Smith et al, ). Indeed, in our study, gender was among the significant predictors.…”
Section: Discussionsupporting
confidence: 93%
“…Among the demographics investigated in the present study, only gender proved to be a predictor of breakfast‐skipping behaviour among adolescents, thus confirming what Shaw () and Fiuza et al () found. Yet contrary to some earlier studies that found demographics such as family income, mothers' education, and a two‐parent family structure to be associated with adolescent eating habits (Lazzeri et al, ; Moreno‐Maldonado et al, ; Smith et al, ), the current study failed to capture these associations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, a high percentage (42.6%) of breakfast omission stands out, higher than that found in other cities in Brazil 15,17,23,24,25,26,27 , but it is worth mentioning that no studies have been conducted in the North and Northeast regions. A study using data from the National School Health Survey (2012) found that 38% of adolescents did not eat breakfast regularly, which was associated with a higher likelihood of having other inappropriate eating habits, such as a diet low in fruits and vegetables and rich in sugars and fried foods 28 .…”
Section: Discussioncontrasting
confidence: 75%